EP1231 Impact of population genetic testing and ovarian cancer risk stratification on the emotional well-being and health of unselected women in a general population. (1st November 2019) - Gaba, F; Liu, X; Chandrasekaran, D; Kalsi, J; Antoniou, A; Side, L; Menon, U; Jacobs, I; Marks, D; Manchanda, R
Abstract : Introduction/Background: Algorithms for predicting ovarian-cancer (OC) risk, have been developed and validated in the 'Predicting-Risk-of-Ovarian-Malignancy-Improved-Screening and Early-detection' (PROMISE) programme. This enables population stratification for OC-risk prediction, screening and prevention. We present the results of a qualitative-study exploring the range of attitudes, experiences and impact on emotional wellbeing, lifestyle and health following unselected panel-genetic-testing (PGT) and OC-risk stratification in unselected women > 18-years ascertained through primary care networks in the PROMISE Feasibility-Study (ISRCTN 54246466 ). This is the first qualitative-study in unselected general-population women undergoing PGT. Qualitative data enables care to be provided according to insights of users by gaining a better understanding of, and reasons for choices made. Methodology: In-depth semi-structured 1:1 interviews were conducted using a pre-developed topic-guide (development informed by literature review and expert consultation) until informational saturation reached. Wording and sequencing of questions were left open with probes used to elicit additional information. All interviews were audio recorded and transcribed verbatim. Questions were fine-tuned during a pilot-interview. Transcripts were analysed using an inductive theoretical framework and data managed using NVIVO-v12. Results: Informational saturation was reached following ten interviews. Eight interconnected themes were identified: health behavioural choices; interest; counselling; decision making; facilitators/barriers determining acceptability; effect of results on health/wellbeing; results communication; satisfaction. Overall satisfaction with PGT/OC risk stratification was high and no interviewees expressed regret. The most important facilitators were ease of testing, learning about children's risk, access and ease of surgical prevention. Barriers included change in family dynamics, insurance, stigmatization, having personality traits associated with stress/worry. Conclusion: Population-based genetic-testing for OC-risk prediction in general-population women is associated with high acceptability and satisfaction. The facilitators and barriers observed are largely similar to those reported with genetic-testing seen in high-risk cancer clinics and unselected testing in the Jewish population. Disclosure: RM declares research funding from Cancer Research UK and The Eve Appeal for the PROMISE Feasibility Study and is Chief Investigator. RM declares research funding from Barts & the London Charity and Rosetrees Trust outside this work, as well as an honorarium for grant review from Israel National Institute for Health Policy Research and honorarium for advisory board membership from Astrazeneca/MSD. RM is supported by an NHS Innovation Accelerator (NIA) Fellowship for population testing. IJ and UM have a financial interest in Abcodia, Ltd., a company formed to develop academic and commercial development of biomarkers for screening and risk prediction. IJ is a member of the board of Abcodia Ltd, a Director of Women's Health Specialists Ltd and received consultancy from Beckton Dickinson. FG is an investigator and the study coordinator for the PROMISE Feasibility study. XL, DC, DM, LS, JK, AA have nothing to declare.